Evaluating guilt and shame in an expressive writing alcohol intervention - Rodriguez, Lindsey M. (Alcohol, 2015)
Expressive writing interventions have shown positive physical and psychological health benefits over time, with the presumed mechanism being emotional disclosure. However, work utilizing expressive writing in behavior change has been minimal. The current research applied the expressive writing paradigm to reduce drinking intentions among college students, and evaluated the role of event-related guilt and shame in intervention effects. College students (N = 429) completed a baseline survey and were randomly assigned to one of three conditions: Negative (write about a heavy drinking event that was negative); Positive (write about a heavy drinking event that was positive); or Neutral (write about their first day of college). After writing, readiness to change and future drinking intentions were assessed. Results revealed intervention effects on intended drinks per week and intended number of drinks during peak and typical drinking occasions. Participants in the negative condition also displayed higher levels of event-related guilt and shame. Results showed that guilt mediated intervention effects on readiness to change, which also mediated the association between guilt-reparative behavior and drinking intentions. Results provide initial support for an expressive writing intervention on alcohol use and underscore the importance of eliciting emotions associated with reparative behavior when considering negative past experiences and future behavior change.